The determinants of job satisfaction among police forces in Ibu Pejabat Polis Daerah (IPD) Mersing / Khairunisa Ghazali @ Sulaiman and Nurul Aniqah Madun - Ghazali @ Sulaiman, Khairunisa; Madun, Nurul Aniqah (Faculty of Business and Management, 2015)
Job satisfaction is one of the methods used to establish and maintain a healthy organizational structure. It has been frequently investigated in studies that deal with organizational strategies because of its potential impact of work attitudes such as job performance, productivity and organizational commitment. Although researchers have identified many factors that relate to job satisfaction, the majority of these factors can be grouped into a category which is environmental factors. Many researcher argue that the work environment is a better predictor of job satisfaction. The purpose of this study is to examine the relationship between environmental factors and job satisfaction among police forces in Ibu Pejabat Polis Daerah (IPD) Mersing. Therefore this study could make important contribution to extant research in management and organizational behavior. In the beginning of this study, the purpose, research question, and the need for the study is given. Then, literature is discussed about job satisfaction and environmental factors that focusing on the relationship between them. The study generated 76 response rate from 92 respondents. The results showed that a salary and fringe benefits, and relationship with co-workers was found to have significant positive relationship with job satisfaction.